2001
DOI: 10.1091/mbc.12.10.2947
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts Act as Specialized Domains for Tetanus Toxin Binding and Internalization into Neurons

Abstract: Tetanus (TeNT) is a zinc protease that blocks neurotransmission by cleaving the synaptic protein vesicle-associated membrane protein/synaptobrevin. Although its intracellular catalytic activity is well established, the mechanism by which this neurotoxin interacts with the neuronal surface is not known. In this study, we characterize p15s, the first plasma membrane TeNT binding proteins and we show that they are glycosylphosphatidylinositol-anchored glycoproteins in nerve growth factor (NGF)-differentiated PC12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 85 publications
(126 reference statements)
9
122
0
6
Order By: Relevance
“…7C). These results are consistent with the existence of heterogeneity among DRMs (58), such that certain types of DRMs may be differentially affected by cholesterol depletion.…”
Section: Analysis Of the Role Of Gpi-anchored Proteins In Vacasupporting
confidence: 88%
See 2 more Smart Citations
“…7C). These results are consistent with the existence of heterogeneity among DRMs (58), such that certain types of DRMs may be differentially affected by cholesterol depletion.…”
Section: Analysis Of the Role Of Gpi-anchored Proteins In Vacasupporting
confidence: 88%
“…Two toxins with intracellular enzymatic activity, cholera toxin and tetanus toxin, bind to GM1 and a specific GPI-anchored protein, respectively, which are enriched in lipid raft microdo- mains (43-45, 58, 67). It has been proposed that lipid rafts play an important role in the internalization and intracellular trafficking of these toxins (44,58,67). The conclusion that these bacterial protein toxins require lipid rafts for intoxication of cells has been based mainly on experiments that utilize cyclodextrin or other cholesterol-interacting drugs to alter lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PC12 cells were grown on poly-L-lysine-coated coverslips and differentiated with 100 ng/ml nerve grow factor in Dulbecco's modified Eagle's medium for 72 h (24).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of synaptotagmins (Syts) I and II as protein receptors for BoNT/B and BoNT/G, and SV2 for BoNT/A supported this concept (15)(16)(17)(18)(19). Recent results (20)(21)(22) suggested that, unlike BoNTs, TeNT uses glycosyl-phosphatidylinositol (GPI)-anchored glycoproteins of neuronal rafts as receptors.…”
mentioning
confidence: 94%